2018
DOI: 10.1017/s0022029918000766
|View full text |Cite
|
Sign up to set email alerts
|

Use of single-step genome-wide association studies for prospecting genomic regions related to milk production and milk quality of buffalo

Abstract: The aim of this research communication was to identify chromosome regions and genes that could be related to milk yield (MY), milk fat (%F) and protein percentage (%P) in Brazilian buffalo cows using information from genotyped and non-genotyped animals. We used the 90 K Axiom® Buffalo Genotyping array. A repeatability model was used. An iterative process was performed to calculate the weights of markers as a function of the squared effects of Single Nucleotide Polymorphism (SNP) and allele frequencies. The 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The previous version of assembly (r1) used in the previous investigations was annotated to bovine genome (UMD31 assembly: see de Camargo et al (2015); Iamartino et al . (2017); da Costa Barros et al (2018); Liu et al . (2018); Herrera et al (2018); El-Halawany et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The previous version of assembly (r1) used in the previous investigations was annotated to bovine genome (UMD31 assembly: see de Camargo et al (2015); Iamartino et al . (2017); da Costa Barros et al (2018); Liu et al . (2018); Herrera et al (2018); El-Halawany et al .…”
Section: Resultsmentioning
confidence: 98%
“…For buffalo, development of Axiom Buffalo Genotyping Array (90k SNPs) opens new opportunities to identify candidate genes associated with buffalo milk production traits and provides the possibility of predicting genomic breeding values for buffalo breeds in different countries. So far, 87 significant and 354 suggestive genomic regions were reported for milk production traits in Brazilian, Chinese, Egyptian, Iranian, Italian and Philippino buffalo (de Camargo et al ., 2015; El-Halawany et al ., 2017; Iamartino et al ., 2017; Mokhber, 2017; da Costa Barros et al ., 2018; Herrera et al ., 2018; Liu et al ., 2018; Abdel-Shafy et al ., 2020; Awad et al ., 2020; Lu et al ., 2020). Despite the fact that these loci were distributed on almost all chromosomes, none of these SNPs were overlapped between studies indicating the complexity of milk production traits and the modest effect of such SNPs (Abdel-Shafy et al ., 2020).…”
mentioning
confidence: 99%
“…Recently, candidate genes harboring single nucleotide polymorphisms (SNP) significantly associated with milk fat content (Li et al, 2018c;Gu et al, 2019), protein percentage (Manzoor et al, 2018(Manzoor et al, , 2020, and fatty acid composition (Cosenza et al, 2017(Cosenza et al, , 2018 have been identified on different buffalo chromosomes. As for milk yield, one of the most important economic traits in buffalo industry, associated polymorphisms have been identified at the whole genome level (Wu et al, 2013;Venturini et al, 2014;de Camargo et al, 2015;Menon et al, 2016;El-Halawany et al, 2017;Iamartino et al, 2017;da Costa Barros et al, 2018;Du et al, 2019). These studies have made great contributions to the progress of various breeding programs in buffalo.…”
Section: Introductionmentioning
confidence: 99%
“…Previous genome-wide association studies for reproductive traits (Camargo et al, 2016;Li et al, 2018) were conducted using the bovine reference genome assembly, and the results are expressed for bovine autosomes (BTA). Compared to the present study, the cited authors also described significant SNPs Neto et al, 2020) and for milk production and quality (Barros et al, 2018) in water buffaloes, making this chromosome interesting in future studies, either to prospect for new markers or to study pleiotropic effects.…”
Section: Re Sults and Discussionmentioning
confidence: 44%
“…The data derived from genome-wide association studies can be used to map causal variants in a genome region and to gain further knowledge about the genetic architecture of traits of interest in animal breeding programs (Goddard, Kemper, MacLeod, Chamberlain, & Hayes, 2016). So far, genome-wide association studies and genomic selection in buffaloes have focused on milk production and its content (Aspilcueta-Borquis et al, 2015;Barros et al, 2018;Camargo et al, 2016;El-Halawany et al, 2017;Liu et al, 2018), and only few studies have investigated reproduction traits (Camargo et al, 2016;Li et al, 2018). Thus, the aim of this study was to identify candidate genes for age at first calving and first calving interval in buffaloes by the single-step GBLUP (ssGBLUP) method using the new assembly of the buffalo genome (UOA_WB_1) as the genomic reference.…”
mentioning
confidence: 99%